Impact of Climate Change on Large Cardamom-Based Livelihoods in Panchthar District, Nepal - Rijal, Shiba Prasad (The Third Pole: Journal of Geography Education, 2014)
The paper aims at analyzing the impact of climate change on large cardamom-based livelihoods in Panchthar district by reviewing literature and compiling perceptions of local people. Large cardamom, a newly introduced high-value cash crop grown in 36 hill and mountain districts in Nepal, is cultivated in all 41 Village Development Committees of Panchthar district concentrating largely in its northern and eastern parts at the elevations of roughly between 500 to 2000 meters above sea level. Though area coverage and production of large cardamom is limited compared to other crops, its contribution on people’s livelihood is significant as it has high market value. Production of large cardamom contributes much on people’s livelihoods as it is the main source of household income and provides seasonal employment to thousands of people from farm to the market. Some local cultural producers have also been using bi-products of large cardamom for production of handicrafts such as baskets, tablemats, bags, and window blinders. Besides, it has numerous indirect implications such as reduction in soil erosion and landslides, and increase in biodiversity and carbon’s tock. In recent years, production of large cardamom has been declining as a result of climate change induced factors. The decline adversely affects people’s livelihoods. DOI: http://dx.doi.org/10.3126/ttp.v13i0.11544 The Third Pole Vol. 13, 2013 page : 33-38